Eukaryotic translation initiation factor 4-γ, 1 gene mutations are rare in Parkinson's disease among Taiwanese - Yi Ching Weng; Chiung Mei Chen; Yi Chun Chen; Hon Chung Fung; Chia Wen Chang; Kuo Hsuan Chang; Yih Ru Wu (Journal of the Formosan Medical Association, 2016)
Parkinson's disease (PD) is the second most common neurodegenerative disorder worldwide. Although idiopathic PD accounts for most of the cases, several genetic mutations have been found to cause PD. Mutations in the eukaryotic translation initiation factor 4-γ, 1 (EIF4G1) gene have been identified since 2011, which were reported to be associated with PD among Caucasians in subsequent research. However, this observation was not consistent. The contribution to other ethnic groups remains limited, with < 1% of sporadic cases. We conducted a case–control study to analyze if EIF4G1 is a risk factor for PD patients in Taiwan. Methods: There were 595 PD patients and 600 controls without neurological diseases enrolled in this study. Four reported mutations—A502V (c.1505C>T), G686C (c.2056 G>T), R1197W (c.3589C>T), and R1205H (c.3614G>A)—were analyzed. Results: There were no mutations found in either PD patients or controls. Conclusion: This study indicates that the EIF4G1 mutation is rare in Taiwan, which is consistent with other reports from Asia. Ethnicity could have a great influence on EIF4G1 in PD. Further large scale studies are warranted to evaluate the association of PD and EIF4G1 gene.